The Influence of Training and Development on Employee Performance in Port of Salalah in the Sultanate of Oman - Hubais M.G.; Islam M.K. (World Scientific and Engineering Academy and Society, 2025)
Salalah Port is considered an important contributor to the economic development of Oman in terms of generating revenue from the non-oil sector and employing local Omanis. This study aims to examine the impact of training and development on employee performance in Salalah Port in Oman. To achieve this objective a positivist research paradigm, a deductive approach, a quantitative research strategy, and a simple random sampling technique were employed. A survey questionnaire instrument was employed to collect data from 219 employees working at Salalah Port in Oman. For analyzing the data, the SPSS v23 was used to test the proposed hypotheses. The revealed results indicated that Training Needs Assessment, Training Method, and Training Effectiveness have a significant on employee performance. However, concluded that training and development play a major role in making employee performance effective and efficient. Effectiveness and efficiency in performing job roles contribute to organizational growth. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.